A new method for next-generation sequencing of the full hepatitis b virus genome from a clinical specimen: Impact for virus genotyping - Hebeler-Barbosa, Flavia [UNESP]; Wolf, Ivan Rodrigo [UNESP]; Valente, Guilherme Targino [UNESP]; Mello, Francisco Campello Do Amaral; Lampe, Elisabeth; Pardini, Maria Inês de Moura Campos [UNESP]; Grotto, Rejane Maria Tommasini [UNESP] (MDPI, 2020)
Hepatitis B virus (HBV) is an enveloped virus that induces chronic liver disease. HBV has been classified into eight genotypes (A–H) according to its genome sequence by using Sanger sequencing or reverse hybridization. Sanger sequencing is often restricted to analyzing the S gene and is inaccurate for detecting minority genetic variants, whereas reverse hybridization detects only known mutations. Next-generation sequencing (NGS) is a robust tool for clinical virology with different protocols available. The objective of this study was to develop a new method for the study of viral genetic polymorphisms or more accurate genotyping using genome amplification followed by NGS. Plasma obtained from five chronically infected HBV individuals was used for viral DNA isolation. HBV full-genome PCR amplification was the enrichment method for NGS. Primers were used to amplify all HBV genotypes in three overlapping amplicons, following a tagmentation step and Illumina NGS. For phylogenetic analysis, sequences were extracted from the HBVdb database. We were able to amplify a full HBV genome; further, NGS was shown to be a robust method and allowed better genotyping, mainly in patients carrying mixed genotypes, classified according to other techniques. This new method may be significant for whole genome analyses, including other viruses.
Keywords: Genotyping; Hepatitis B virus; NGS; Phylogeny analysis